IMPLEMENTASI BERPIKIR POSITIF DALAM BUKU “TERAPI BERPIKIR POSITIF KARYA DR. IBRAHIM ELFIKY” DALAM BIMBINGAN KONSELING BERKEBUTUHAN KHUSUS - Denis Hartati (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2018)
Positive thinking is an important thing to be applied by humans because positive thinking can affect the actions we do. However, now many people prefer to think negatively than think positively. So, problems often arise as a result of not thinking positively, especially related to self-confidence. This problem does not only appear in normal people who have good physical condition but also appear in children with special needs, especially those with blind people. This study aims to implement positive thinking steps in counseling guidance with special needs especially to foster a sense of confidence in the blind. The research method used in this study is library research. The subjects in this study were books “Terapi Berpikir Positif (Biarkan Mukjizat dalam Diri Anda Melesat Agar Hidup Lebih Sukses dan Lebih Bahagia) by Dr. Ibrahim Elfiky. Data collection using documentation method. The results of the data from this study used qualitative descriptive analysis that is data collected, processed, and presented, then concluded. The results of this study are that positive thinking can be implemented for blind children in fostering their self-confidence by joining or mingling with people who are physically normal, eliminating negative thought that blind people are looked down on by normal people and of course applying positive thoughts to the blind, so that his confidence will increase.